The Role of Ferritin Serum Level as Predictor Sepsis Mortality on Children in Dr. Moewardi Hospital of Surakarta - Sucianto, Agus; Pudjiastuti, Pudjiastuti; Kawuryan, Diah Lintang (Journal of Maternal and Child Health, 2023)
Background: Sepsis cause death in the worldwide pediatric population. Eestablishing the diagnosis of sepsis in children is challenging because the symptoms are varied and not specific. Serum ferritin is an acute phase protein which can be elevated in sepsis. This study aimed to determine the role of ferritin level as a predictor for sepsis mortality in pediatric patient Subjects and Method: A cross sectional study was conducted in children aged between 1 months and 18 years old diagnosed with sepsis who were treated at Dr. Moewardi General Hospital, Surakarta from November 2021 to April 2022.  The statistical analysis used SPSS 25 with p<0.05 was considered significant. The cut off point of serum ferritin level was determined with  ROC curve. Results: A cross sectional study was conducted in children aged between 1 months and 18 years old diagnosed with sepsis who were treated at Dr. Moewardi General Hospital, Surakarta from November 2021 to April 2022.  The statistical analysis used SPSS 25 with p<0.05 was considered significant. The cut off point of serum ferritin level was determined with  ROC curve. Conclusion: Serum ferritin level can be predictor of mortality in children with sepsis. Keywords: ferritin, mortality in sepsis, children. Correspondence: Agus Sucianto. Department of Pediatrics, Sebelas Maret University/ Dr. Moewardi General Hospital, Surakarta, Central Java, Indonesia. Kolonel Sutarto Street No. 132, Surakarta, Indonesia. Email: sucianto22@gmail.com. Mobile: 081227595134.